Measuring Translation Competence Acquisition - Orozco, Mariana; Hurtado Albir, Amparo (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2002)
AbstractThe following article describes the development of instruments for measuring the process of acquiring translation competence in written translation. Translation competence and its process of acquisition are firstly described, and then the lack of empirical research in our field is tackled. Thirdly, three measuring instruments especially developed to measure translation competence acquisition are presented: (i) to measure notions about translation, (ii) to measure students’ behaviour when faced with translation problems, and (iii) to measure errors. Pilot studies were carried out for three years to test, improve and validate the measuring instruments. Finally, a future research project, which shows a possible application of the measuring instruments, is presented, and the main elements of the research project are described: the construct, dependent and independent variables, hypotheses, moments of measurements and the samples to be used.